Methods of green synthesis of Au NCs with emphasis on their morphology: A mini-review. Issue 6 (June 2021) - Sayadi, Khali; Akbarzadeh, Fatemeh; Pourmardan, Vahid; Saravani-Aval, Mehdi; Sayadi, Jalis; Chauhan, Narendra Pal Singh; Sargazi, Ghasem
Abstract: Greener synthetic methods are becoming more popular as a means of reducing environmental pollution caused by reaction byproducts. Another important advantage of green methods is their low cost and the abundance of raw materials. Herein, we investigate the green Au nanoclusters (NCs) using microorganisms (bacteria and fungi) and plant extraction with various shapes and development routes. Natural products derived from plants, tea, coffee, banana, simple amino acids, enzyme, sugar, and glucose have been used as reductants and as capping agents during synthesis in literature. The synthesis techniques are generally chemical, physical and green methods. Green synthesis of Au NCs using bacteria and fungi can be divided into intracellular and extracellular. In an intracellular manner, bacterial cells are implanted in a culture medium containing salt and heated under suitable growth conditions. However, in an extracellular manner, the Au ions are directed from the outside into the cell. Thus, these methods are considered as a better alternative to chemical and physical synthesis. The research on green synthesis of Au nanoparticles (NPs) and its influence on their size and morphology are summarized in this review. Abstract : Au nanostructures, Green synthesis, Intracellular, Extracellular.